TH Selbon Tower, Kuala Lumpur / Andrea Daling ... [et al.] - Andrea, Daling; Haizad Hafiz, Hairudin; Muhammad Saiful Ikhwan, Awang; Nursyaryana, Jamaludin; Sabrina, Misor (2019)
Integrated Final Project (IFP) is the most important report that should be prepared by the final year students of AP119 Diploma program. A group of student has to study and analyze the maintenance organization or company manage in a case study building, and shall relate the data with their knowledge in how to build a well maintenance organization. At the end of this study, students would be able to identify the strength and weakness of the organization that may emphasis to the property maintenance management. Final Project is a subject comprising of various aspects of the building industry. This project consists of 9 chapter which overall will conclude to a conclusion related to the maintenance organization selected for this project. In chapter 1, we will review and discuss about the details of the property for example the background of the company and the case study, the list of major occupants, the facilities and building services provided in the building and also the surrounding building for the case study. In chapter 2, we have to describe the organization objectives at the building and identify the type of organization structure as to describe the scope and responsibility of each position of the maintenance organization. In maintenance policy, planning and programme which is in chapter 3, students need to identify and describe the maintenance division vision, mission and objectives. Other than that, the maintenance and quality policy, maintenance standard, quality standard also need to be identified to determine the allocation of the maintenance strategies such as maintenance planning and maintenance programme. Next, for chapter 4 which is building design and technology, we need to identify the building design and concept, green sustainable initiative that provided in the building and describe the building elements and specifications such as sub-structure, super structure, and internal finishes. Students also shall cover the building services, facilities, external works, special technologies and features provided in the building. xxvi Moving on to the next chapter which is chapter 5, condition assessment of the building. Students need to evaluate the current condition of the building using Building Condition Assessment Rating System (BCARS) and identify the limitation space. The building defects must be analyzed and the remedial work must be recommended thus the rectification cost must be calculated based current on schedule of rate which is ‘Jadual Kadar Harga’ edition 2014 and 2016 by JKR. Furthermore, in chapter 6 we need to make an overview and discuss about maintenance strategy implemented by the maintenance organization. Other than that, students need to analyze the tenancy agreement, building services contract, and laws and regulations that have been used in the building in chapter 7. For the chapter 8, we also have to identify and analyze the maintenance budget used by the maintenance organization and determine the forecast budget for 3 years ahead. Last but not least, in the final chapter which is chapter 9, problems and recommendations. Students need to identify the problems in chapter 1 to chapter 8 and recommend ways to overcome the problems. Students also need to make conclusion of overall chapter that have been covered for the building.